Pengaruh Substrat Dasar yang Berbeda pada Sistem Resirkulasi terhadap Fisiologis Teripang Lokal (Phyllophorus sp.) selama Masa Adaptasi [Effect of Different Substrates on the Recirculation System for Local Sea Cucumber (Phyllophorus sp.) Physiological During Adaptation Period ] - Sri Subekti; Tegar Putra Purnayudha; Endang Dewi Masithah (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract This study aims to determine the physiological changes in local sea cucumber (Phyllophorus sp.) Were adapted on a maintenance bath recirculation system with a different substrate. This study uses three treatments and three replications. The first treatment is by using sea mud substrate, a second treatment using fine gravel substrate, a third treatment was not using the base substrate. The main parameters of physiological changes observed were local sea cucumber (Phyllophorus sp.) During the period of adaptation in maintenance bath. Supporting parameters observed were mortality rate and water quality. The results showed that physiological changes occur during adaptation changes of sea cucumber body to rounded, elongated, expanded and irregular. Sea cucumbers secrete intestines and gonads in stress response to environment. Sea cucumbers are maintained on the mud substrat was average survive for five days, fine gravel substrate for three days and without substrate for less than three days. The conclusion of this research is maintained in bath of sea cucumbers with sea mud substrate showed the best results, it is characterized by the average survival time longer and the amount of sea cucumber intestines and gonads secrete less of a sea cucumber that are maintained on the basis of substrate fine gravel substrate and without substrate.